Shanxi lignite efficient degrading bacterium screened from tremella fuciformis seeds
By screening out the T. tangerine green strain from the T. argillus seeds and degrading lignite under specific conditions, the problem of low utilization efficiency of medium and low-level coal resources in the prior art was solved, and an efficient and environmentally friendly degradation effect was achieved.
Patent Information
- Application Number
- CN202311206214.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to efficiently utilize low-level coal resources, especially Shanxi lignite, and microbial degradation methods have problems of high energy consumption and serious emissions.
A strain that efficiently degrades lignite was screened from Tremella seeds, specifically Trichoderma citrinoviride. This strain was prepared and preserved, and lignite degradation experiments were performed under specific conditions.
The efficient degradation of Shanxi lignite after pretreatment of H2O2 was achieved, with a degradation rate of (44.34±0.47)%, while reducing energy consumption and emissions.
Smart Images

Figure CN119662413A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental biology research and relates to the breeding of a Shanxi lignite-degrading bacterium, in particular to a strain of Shanxi lignite-degrading bacterium (hereinafter referred to as lignite) screened from Tremella fuciformis seeds. Background Art
[0002] Coal is an important energy reserve in my country, of which lignite accounts for 1 / 3 of the coal reserves. This part of lignite has a large reserve and low calorific value, and its combustion and utilization have serious environmental emissions. How to make full use of this part of low-grade coal resources and make them fully resource-oriented, which can not only solve the pollution emission problem but also realize the high added value utilization of low-grade coal, has received widespread attention from researchers. Using lignite as raw material to produce chemical raw materials or energy is an effective way to realize the comprehensive utilization of lignite resources. The first step in the utilization of lignite is the liquefaction of lignite. The main liquefaction methods are physical and chemical methods, but there are problems of high emissions and high energy consumption. The efficient conversion and utilization of lignite through microbial degradation is an important research content in the field of environmental biology.
[0003] Studies have shown that there are two main ways to screen low-rank coal-degrading bacteria: one is to directly extract and isolate microorganisms from coal, mine water, soil samples in mining areas, and natural environments in mining areas that are exposed to nature, that is, to directly isolate strains that adapt to the coal environment from the coal environment to degrade low-rank coal; the other is to screen out microorganisms that can degrade organic compound components such as lignin and polycyclic aromatic hydrocarbons in low-rank coal, thereby achieving efficient degradation of low-rank coal. Among them, the chemical structure of lignite is similar to lignin. Based on this, it is reasonable to infer that microorganisms that degrade lignin also have the ability to degrade lignite and have an efficient degradation effect on lignite. In most experiments on biodegradable coal, the presence or absence of strains that can degrade lignin plays a vital role in the effective degradation of coal. Tremella fuciformis can survive on sawdust as a carbon source, but Tremella fuciformis hyphae itself has almost no ability to degrade lignin, but the strains that grow with Tremella fuciformis play a major role. Therefore, it is of great significance to isolate a strain that can efficiently degrade lignite from Tremella fuciformis seeds. Summary of the invention
[0004] The invention aims to provide a lignite-degrading bacterium screened from Tremella fuciformis seeds, wherein the bacterium is Trichoderma citrinoviride.
[0005] The present invention adopts the following technical solutions:
[0006] A strain selected from Tremella fuciformis seeds for degrading lignite is Trichoderma citri noviride.
[0007] The preparation method of the above-mentioned strain for efficiently degrading lignite has the following specific preparation steps:
[0008] (1) Weigh 5 g of Tremella fuciformis seeds, place them in a conical flask, add 1000 ml of physiological saline, and mix thoroughly to prepare a bacterial suspension. Then, take 1 ml of the original solution from the obtained bacterial suspension and place it in a test tube, add 9 ml of physiological saline, and mix well to form a 10 -2 of bacterial suspension dilution; then from 10 -2 Take 1 ml of the diluent and add it to a test tube containing 9 ml of saline. Mix well to form a 10 -3 The bacterial suspension was diluted to 10 -2 , 10 -3 , 10 -4 and 10 -5 of dilution.
[0009] (2) Then, sterilized potato dextrose agar (PDA) medium (200 g potato, 20 g glucose, 20 g agar and 1000 ml distilled water) was poured into a sterile petri dish and cooled to solidify to prepare a sterile plate. -2 , 10 -3 , 10 -4 and 10 -5 1 μl of the dilution was respectively drawn and dropped on the surface of the sterile plate, and then evenly spread with a sterile spreader. After the spreading was completed, the culture medium was inverted and cultured in a biochemical incubator at 27°C for 2 days, and observed every 4 hours. Single colonies of different forms on the plate were picked out from the strains and cultured on potato dextrose agar medium for multiple times until pure strains were obtained. After preliminary screening, 3 pure strains were obtained.
[0010] (3) Rescreening of lignite-degrading bacteria: The three strains obtained from the initial screening were inoculated into a modified potato dextrose agar medium (modified PDA medium) supplemented with coal as a carbon source and cultured for 4 consecutive days. Among them, the strain that can grow well on the medium, with the overall colony showing green color and the tissue shape of the colony being cotton-like, is the rescreened strain A-1. Figure 1 .
[0011] (4) Preservation of lignite-degrading bacteria: The strains obtained by repeated screening were inoculated onto slant culture medium and cultured in a biochemical incubator. After the strains were fully grown, they were stored in a refrigerator at 4°C. Every 3-6 months, they were transferred to new slant culture medium, cultured for 24 hours, and stored at -18°C.
[0012] (5) The above-mentioned culture medium formula is as follows: PDA medium: 200g potato, 20g glucose, 20g agar, 1000ml H2O2, natural pH, sterilization at 121℃ for 20 minutes; modified PDA medium: 200g potato, 20g coal powder, 20g agar, 1000ml H2O2, natural pH, sterilization at 121℃ for 20 minutes; preservation medium: strain A-1 uses modified PDA medium slant culture medium.
[0013] The advantages of the present invention are:
[0014] (1) For the first time, a strain that can efficiently degrade Shanxi lignite was screened from Tremella fuciformis seeds.
[0015] (2) The degradation rate of the strain of the present invention on Shanxi lignite pretreated with H2O2 reached (44.34±0.47)% under the conditions of temperature of 25°C and rotation speed of 150 rpm for 20 days. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Individual morphology and growth status of strain A-1 on improved PDA medium
[0017] Figure 2 Growth status of strain A-1 during the degradation of coal samples pretreated with H2O2 (A: when a small number of droplets appear; B: when a large number of droplets appear)
[0018] Figure 3 Agarose gel electrophoresis results of PCR amplification products of strain A-1
[0019] Figure 4 Biodegradation effect of strain A-1 on Shanxi lignite pretreated with H2O2
[0020] Figure 5 Plackett-Burman test influencing factors and level settings
[0021] Figure 6 Plackett-Burman test conditions and results
[0022] Figure 7 Plackett-Burman model effect value and significance analysis results
[0023] Figure 8 Semi-normal distribution result diagram (the farther away from the central axis, the more significant the impact on the degradation rate of Shanxi lignite)
[0024] Fig. 9 Influencing factors and level settings of response surface experiment
[0025] Fig.10Response surface test conditions, predicted values and test results
[0026] Fig.11 Response surface and contour plots of Y=F(B,A)
[0027] Fig.12 Response surface and contour plots of Y=F(B,E)
[0028] Fig.13 Response surface and contour plots of Y=F(A,E)
[0029] Implementation process
[0030] The implementation process of the present invention is described in detail below in conjunction with specific embodiments, but the scope of protection claimed by the present invention is not limited to the scope described in the embodiments.
[0031] The sources of raw materials or preparations used in the following examples are:
[0032] The lignite sample used in the present invention comes from Datong Coal Mine in Shanxi Province. First, the coal block is crushed and the coal particles with a particle size of 0.1-0.125 mm are selected as the test raw coal. The raw coal is mixed with 30% H2O2 at a ratio of 1g:10ml, then stirred in a magnetic stirrer for 10 hours, rinsed with deionized water until the pH of the filtrate is neutral, dried in an oven at 80°C for 48 hours, and stored in a brown reagent bottle at room temperature for later use.
[0033] In the following examples, the methods used are all conventional methods, and the specifications of the reagents used are all analytical grade (AR), wherein NaNO3, K2HPO4, MgSO4·7H2O, and KCl are from Tianjin Fuchen Chemical Reagent Factory, C5H8NNaO4 (sodium glutamate) is from Shanghai Aladdin Biochemical Technology Co., Ltd., and glucose and agar are from Tianjin Komiou Chemical Reagent Co., Ltd.
[0034] Example 1: Screening and identification of lignite-degrading strains
[0035] (1) Preliminary screening of lignite-degrading bacteria
[0036] Weigh 5g of Tremella fuciformis seeds, place them in a conical flask, add 1000ml of saline solution, and mix thoroughly to prepare a bacterial suspension. Then, take 1ml of the stock solution from the obtained bacterial suspension and place it in a test tube, add 9ml of saline solution, and mix well to form a 10 -2 of bacterial suspension dilution; then from 10 -2 Take 1 ml of the diluent and add it to a test tube containing 9 ml of saline. Mix well to form a 10 -3 The bacterial suspension was diluted to 10 -2 , 10 -3, 10 -4 and 10 -5 of dilution.
[0037] Then, the sterilized potato dextrose agar (PDA) medium was poured into a sterile culture dish and cooled and solidified to make a sterile plate. -2 , 10 -3 , 10 -4 and 10 -5 1 μl of the dilution solution was respectively drawn and dropped on the surface of the sterile plate, and then evenly spread with a sterile spreader. After the spreading was completed, the culture medium was inverted and cultured in a biochemical incubator at 27°C for 2 days, and observed every 4 hours. Single colonies of different forms on the plate were picked out from the strains and cultured on potato dextrose agar medium for multiple times until a pure strain was obtained. The pure strain was obtained by preliminary screening.
[0038] The formula of potato dextrose agar medium (PDA) is 200g potato, 20g glucose, 20g agar, 1000ml H2O2, natural pH, and sterilization at 121°C for 20 minutes.
[0039] (2) Rescreening of lignite-degrading bacteria
[0040] The strains screened initially were inoculated into a modified PDA medium supplemented with coal as a carbon source and cultured for 4 consecutive days. The growth of the strains was as follows: Figure 1 The strain A-1 was the one that could grow well on the culture medium, the overall colony gradually turned green, and the tissue shape of the colony was cotton-like.
[0041] The modified PDA medium with coal added as a carbon source has a formula of 200 g potato, 20 g coal powder, 20 g agar, 1000 ml H2O2, natural pH, 121°C, and sterilization for 20 minutes.
[0042] (3) Preservation of lignite-degrading bacteria: The strains obtained by repeated screening were inoculated on slant culture medium and cultured in a biochemical incubator. After the strains were fully grown, they were stored in a refrigerator at -18°C. Every 3-6 months, they were transferred to new slant culture medium, cultured again, and preserved.
[0043] The preservation medium was modified PDA slant medium.
[0044] (4) Experiment on microbial degradation of lignite:
[0045] Prepare several PDA flat solid culture media and inoculate them with Trichoderma viridis under sterile conditions. After inoculation, place them in an intelligent light incubator and activate and culture them at 28°C for three days. Select several plates with similar growth of Trichoderma viridis for experiments. After the coal sample is pretreated with H2O2 and sterilized with ultraviolet light, weigh 0.5 g and sprinkle it evenly on the Trichoderma viridis that has been activated and cultured for three days under sterile conditions. Put the culture dish sprinkled with the coal sample back into the intelligent light incubator and continue to culture it at 28°C. Observe and record the droplet generation on the surface of the coal sample in the culture dish every day, and record the culture time when a small amount of droplets first appear on the surface of the coal powder of each experimental group and the control group. Figure 2 .
[0046] (5) Identification of lignite-degrading strains
[0047] The strain A-1 was identified by molecular biological identification method and sent to Treasure Biotechnology (Dalian) Co., Ltd. for fungal 26S D1 / D2 region sequence analysis.
[0048] The electrophoresis results of the PCR amplification products of strain A-1 are as follows: Figure 3 shown. Figure 3 In (a), “M” represents DL2000 DNA Marker, and “1” represents CT10803-1-PCR product. Figure 3 (b) is the DL2000 band distribution diagram.
[0049] The strain A-1 was sequenced and a partial nucleotide sequence was obtained, as follows:
[0050]
[0051] Example 2: Lignite Degradation Efficiency of Lignite Degrading Bacteria
[0052] First, the selected Trichoderma A-1 was inoculated on the PDA medium for 48h activation culture, and then 0.9% physiological saline was added to form a bacterial suspension for standby use. Take 20 conical flasks with a capacity of 100ml, wash and dry them, add 0.5g of lignite sample pretreated with H2O2 and 50ml of improved DOX medium to 20 conical flasks, seal all conical flasks, and then sterilize them at 121℃ in an autoclave for 20min. After sterilization, 4ml of bacterial suspension was added to the conical flasks respectively, and cultured at 25℃ and 150rpm shaking table for 20 days. At the same time, two groups of control experiments were set up. No bacterial suspension was added to the first control group to test whether the improved DOX medium could degrade lignite particles to produce liquid products; no lignite sample was added to the second control group, and sampling, filtering, and residue collection were performed every day to remove the residual mycelium in the coal-soluble product, and the residual coal was washed with distilled water, dried, and weighed to calculate the degradation rate. The lignite degradation rate P is calculated by the following formula:
[0053]
[0054] Where P is the lignite degradation rate; w0 is the initial weight of lignite powder (g), which is 0.5 g in this experiment; w1 is the weight of residual lignite powder after microbial degradation culture (g).
[0055] The formula of potato dextrose agar (PDA) medium is: 200g potato, 20g glucose, 20g agar, 1000ml H2O2, natural pH, sterilization at 121℃ for 20 minutes; the formula of modified DOX medium is 2g C5H8NNaO4 (monosodium glutamate), 3g NaNO3, 2g K2HPO4, 0.5g MgSO4·7H2O, 0.5g KCl, 1000ml H2O, natural pH, sterilization at 121℃ for 20 minutes.
[0056] Degradation time and degradation efficiency see Figure 4 As can be seen from the figure, with the increase of degradation time, the coal degradation rate also gradually increases. When it is about 20 days, the coal degradation rate tends to be stable. That is, the degradation efficiency of the lignite pretreated with H2O2 by the bacteria within 20 days is determined by the differential weight method to be 35%.
[0057] Example 3: Optimization of lignite degradation rate of lignite-degrading strains
[0058] The degradation efficiency of lignite was optimized by using the determination and calculation method of lignite degradation rate in Example 2. Plackett-Burman design was performed on six factors that affect the degradation rate of Shanxi lignite by Trichoderma citriodora, including ambient temperature (A), ambient pH value (B), inoculation amount (C), coal sample particle size (D), coal slurry concentration (E) and degradation time (F). The influencing factor settings and level settings are as follows: Figure 5 shown.
[0059] Application software Design Expert 12.0, according to Figure 4 The influencing factors and levels of the Plackett-Burman test were set, and the Plackett-Burman test module was created. The high and low levels of a total of 6 influencing factors were set, and 12 groups of test conditions under different extraction conditions were created. The experiment was carried out strictly according to the 12 groups of different conditions generated by the software, and the degradation rate of Shanxi lignite under each group of experimental conditions was calculated. Each group of experiments was repeated three times, and the degradation rate results of Shanxi lignite were averaged. The results of the 12 groups of Plackett-Burman tests generated by the software Design Expert 12.0 are shown in Figure 6 shown.
[0060] The degradation rate of Shanxi lignite (%) was used as the index, and the experimental result data were processed using the software Design Expert 12.0. The regression equation coefficients and significance test results of the six experimental influencing factors on the degradation rate of Shanxi lignite are shown in the figure below: Figure 7 As shown in Figure 2, the semi-normal distribution results of the six experimental influencing factors on the degradation rate of Shanxi lignite are shown in Figure 2. Figure 8 The farther away from the central axis, the more significant the impact on the degradation rate of Shanxi lignite.
[0061] according to Figure 7 and Figure 8 It can be seen that the significant P value of the model is 0.0120 (P < 0.05), which shows that the model has significant influence, so the results of the model data analysis are reliable. Among the six experimental influencing factors, the order of influence on the degradation rate of Shanxi lignite is B>A>E>F>C>D, among which the environmental pH value (B) has the most significant effect on the degradation rate of Shanxi lignite (P < 0.01), and the environmental temperature (A) and coal slurry concentration (E) have a relatively significant effect on the degradation rate of Shanxi lignite (P < 0.05).
[0062] Environmental pH value (B), ambient temperature (A) and coal slurry concentration (E) were selected as factors, and the degradation rate of Shanxi lignite by Trichoderma citriodora was used as the response value to conduct response surface experiment design. Fig. 9 shown.
[0063] The software Design Expert 12.0 was used to create a response surface test module. 17 groups of tests were conducted under different conditions. The experiments were conducted strictly according to the 17 different conditions generated by the software. The degradation rate of Shanxi lignite under each group of experimental conditions was calculated. Each group of experiments was repeated three times, and the results of the Shanxi lignite degradation rate were averaged. The predicted values of the response surface test results generated by the software Design Expert 12.0 and the measured values are shown in Figure 2. Fig.10 shown.
[0064] After analysis, the fitness fitting degree of the response surface model is good, and it can be used as a prediction model for the degradation rate of Shanxi lignite by Trichoderma citriodora under different extraction conditions. The software Design Expert 12.0 was used to further obtain the relationship between the interaction of the three experimental influencing factors and the response value, thereby obtaining the response surface and contour map of the interaction between environmental pH value (B), ambient temperature (A) and coal slurry concentration (E) on the degradation rate of Shanxi lignite by Trichoderma citriodora ( Figures 11 to 13 ).
[0065] Using the software Design Expert 12.0, the quadratic model regression equation of Shanxi lignite degradation rate (Y) and environmental pH value (B), ambient temperature (A), and coal slurry concentration (E) is obtained as follows:
[0066] Y=(0.4299+0.0482B+0.0143A+0.0082E-0.0067BA+0.0001BE+0.0113AE-0.0558B 2 -0.0585A 2 -0.0403E 2 )×100%
[0067] Wherein, Y is the degradation rate of Shanxi lignite; B is the environmental pH value (converted according to the horizontal setting); A is the ambient temperature (converted according to the horizontal setting); E is the coal slurry concentration (converted according to the horizontal setting).
[0068] The optimal extraction conditions for the degradation of Shanxi lignite by Trichoderma citrinodiflora were analyzed by the software Design Expert 12.0: environmental pH value 0.481 (pH = 6.481), environmental temperature 0.092 (28.368 ° C), coal slurry concentration 0.050 (1.0125 g·50 mL -1 ), at this time the predicted degradation rate of Shanxi lignite is 44.106%.
[0069] Combined with the actual conditions of laboratory experimental equipment and facilities, the optimal degradation process conditions were revised to: ambient temperature 28.4℃, ambient pH 6.48, inoculation volume 3mL, coal sample particle size 120-150 mesh, coal slurry concentration 1.0125g·50mL-1 , degradation time 24 days. The experiment was carried out strictly according to the modified optimal degradation process conditions. At this time, the actual degradation rate of Shanxi lignite by Trichoderma citriodora was (44.34±0.47)%, which was consistent with the predicted value of the established model.
Claims
1. A fungus capable of degrading Shanxi lignite (hereinafter referred to as lignite), characterized by: A fungus strain isolated from Tremella fuciformis seeds was numbered A-1 and was identified as Trichoderma citri noviride by sequencing of 26S r DNA D1 / D2 region, belonging to Trichoderma spp.
2. The method for preparing the strain according to claim 1 comprises the following steps: (1) Initial screening of lignite-degrading bacteria: Weigh 5 g of Tremella fuciformis seeds, place them in a conical flask, add 1000 ml of physiological saline, and mix thoroughly to prepare a bacterial suspension. Then, take 1 ml of the original solution from the obtained bacterial suspension and place it in a test tube, add 9 ml of physiological saline, and mix well to form a 10 -2 of bacterial suspension dilution; then from 10 -2 Take 1 ml of the diluent and add it to a test tube containing 9 ml of saline. Mix well to form a 10 -3 The bacterial suspension was diluted to 10 -2 , 10 -3 , 10 -4 and 10 -5 Then pour the sterilized potato dextrose agar medium into a sterile petri dish and make a sterile plate after cooling and solidification. -2 , 10 -3 , 10 -4 and 10 -5 1 μl of the dilution solution was respectively drawn and dropped on the surface of the sterile plate, and evenly spread with a sterile spreader. After the spreading was completed, the culture medium was inverted and cultured in a biochemical incubator at 27°C for 2 days, and observed every 4 hours. Single colonies of different forms on the plate were picked out from the strains and cultured on potato dextrose agar medium for multiple times until pure strains were obtained. Three pure strains were obtained by preliminary screening. (2) Rescreening of lignite-degrading bacteria: The three strains obtained from the initial screening were inoculated into a modified potato dextrose agar medium with coal as the added carbon source and cultured continuously for 4 days. Among them, the strain that can grow on the culture medium, with the overall colony showing green color during the culture process and the tissue shape of the colony being cotton-like, is the rescreened strain A-1. This strain was inoculated onto a slant culture medium and cultured in a biochemical incubator to allow the strain to grow fully, and then the cultured strain was stored in a refrigerator at 4°C. Every 3-6 months, it was transferred to a new slant culture medium, cultured for 24 hours, and stored at -18°C.
3. The preparation method of the bacterial strain for degrading Shanxi lignite according to claim 2, characterized in that: The formula of the modified potato dextrose agar medium with coal as the added carbon source in (1) is: 200 g potato, 20 g coal powder, 20 g agar, 1000 ml H2O2, natural pH, and sterilization at 121°C for 20 minutes.